PENGARUH JUMLAH PRODUKSI, KURS DOLLAR AMERIKA SERIKAT DAN CADANGAN DEVISA TERHADAP EKSPOR JAHE DI INDONESIA - Djohan, Dhian Aswithary; Sudirman, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Export is the activity of selling goods and services abroad. One of the commodities exported from plantation products in Indonesia is Ginger. Ginger is a medicinal plant that has many kasiat, can be used as a spice ingredients and can also be made into drugs. This study aims first to analyze and to know the effect of production amount, US dollar exchange rate and foreign exchange reserves to export ginger in Indonesia simultaneously and partially. Second, to know which variables dominantly influence the ups and downs of ginger exports in Indonesia. Data used in this research is secondary data. Data collection was done by non participant observation. Multiple regression analysis techniques were previously equipped with the classical assumption test. The results of the test with Eviews 8 obtained the result of the production quantity partially and significantly affect the export of ginger in Indonesia. The US dollar exchange rate significantly negatively affected the export of ginger in Indonesia. The number of production is the dominant variable that has the most dominant effect on the increase of export in Indonesia.